Reticulocyte hemoglobin content: a new frontier in iron deficiency diagnostics for major surgical patients - Suma Choorapoikayil; Mischa J. Kotlyar; Lisa Kawohl; Paul P. Pratz; Denana Mehic; Peter Kranke; Florian Rumpf; Lea V. Blum; Jan A. Kloka; Kai Zacharowski; Vanessa Neef; Patrick Meybohm (BMC Anesthesiology)
Abstract Background Iron deficiency (ID) is the most common nutritional deficiency among patients undergoing major surgery. Treatment of ID is straightforward, however implementing a comprehensive anemia management strategy within clinical routines is complex. Recently, reticulocyte hemoglobin content (Ret-He) has been evaluated as an early marker for ID diagnosis. Method In this retrospective study, 2,966 major surgical patients from two University Hospitals were screened for the presence of ID and the significance of Ret-He in diagnosis ID was evaluated in both non-anemic and anemic patients. According to hemoglobin, ferritin, and transferrin saturation concentrations patients were assigned to a Control group (no anemia, no ID), ID group (no anemia, ID), IDA group (anemia, ID) or Others group (anemia, no ID). Results In total, 2,760 patients were included in analysis: Control (n = 1500; 54.2%), IDA (n = 412; 14.9%), ID (n = 487; 17.6%), and Others (n = 370; 13.4%). Ret-He was significantly decreased in the IDA group compared to ID, Control and Others, respectively (p < 0.001). The ROC curve analysis revealed an AUC of 0.842 (95% CI (0.82–0.87)) at Ret-He cutoff 33.5 pg, by which IDA was discriminated with 69.7% (95% CI (65.3–74.0%)) sensitivity and 85.7% (95% CI (82.3-86.1%)) specificity. Of the 370 patients with anemia of unknown cause (Others group) 131 had Ret-He levels < 33.5 pg. In these patients, the median values for ferritin was 492.0 ng/ml (333.5; 818.5 ng/ml) and transferrin saturation 11.9% (18.0; 23.3%). Logistic regression identified significant predictors of ID, with each decrease in Hb and Ret-He associated with a 19.4% (OR = 0.806; p < 0.001) and 26% (OR = 0.740; p < 0.001) increase in the odds of ID, respectively. Conclusion This study highlights the potential of Ret-He as a promising alternative marker for diagnosing ID in patients undergoing major surgery, particularly in cases of elevated ferritin levels or non-anemic patients. Ret-He may serve as a valuable tool to prioritize patients for further iron status testing, especially when preoperative time is limited.